Injectable click-crosslinked hydrogel containing resveratrol to improve the therapeutic effect in triple negative breast cancer - Shin, Gi Ru; Kim, Hee Eun; Ju, Hyeon Jin; Kim, Jae Ho; Choi, Sangdun; Choi, Hak Soo; Kim, Moon Suk (Materials Today Bio, 2022)
Triple-negative breast cancer (TNBC) patients are considered intractable, as this disease has few effective treatments and a very poor prognosis even in its early stages. Here, intratumoral therapy with resveratrol (Res), which has anticancer and metastasis inhibitory effects, was proposed for the effective treatment of TNBC. An injectable Res-loaded click-crosslinked hyaluronic acid (Res-Cx-HA) hydrogel was designed and intratumorally injected to generate a Res-Cx-HA depot inside the tumor. The Res-Cx-HA formulation exhibited good injectability into the tumor tissue, quick depot formation inside the tumor, and the depot remained inside the injected tumor for extended periods. In vivo formed Res-Cx-HA depots sustained Res inside the tumor for extended periods. More importantly, the bioavailability and therapeutic efficacy of Res remained almost exclusively within the tumor and not in other organs. Intratumoral injection of Res-Cx-HA in animal models resulted in significant negative tumor growth rates (i.e., the tumor volume decreased over time) coupled with large apoptotic cells and limited angiogenesis in tumors. Therefore, Res-Cx-HA intratumoral injection is a promising way to treat TNBC patients with high efficacy and minimal adverse effects.
Keywords: Cancer patients; Click-crosslinking; Cross-linked hydrogels; Crosslinked; Inhibitory effect; Injectable hydrogels; Injectables; Intratumoral injection; Therapeutic effects; Triple-negative breast cancers; Click-crosslinking; Injectable hydrogel; Intratumoral injection; Resveratrol; Triple-negative breast cancer